Personalised community maps. (2017) - Ardissono, Liliana; Lucenteforte, Maurizio; Mauro, Noemi; Savoca, Adriano; Voghera, Angioletta
With the convergence of geographical information systems (GIS) and internet technology, the public administration is starting to use online maps as a web-based bidirectional communication channel with the population: maps are used: i) in public portals, for publishing and crowdsourcing information about the territory; ii) in policy-making, for defining a community vision of the territory and for involving people in public choices. Both cases raise challenges related to the large amount of data handled in the maps, and to their lack of group collaboration support. We attempted to address these issues by developing an information-sharing model, and a testbed software application, that support group management and the generation of persistent, custom community maps focused on the user's interests. Our model builds on tag-based user profiles and on information filtering. This paper describes our model and the results of an evaluation of the GroupMapping application, based on it.